(untitled) (Bangladesh Pharmaceutical Journal, 2016)
A computational study of medium effect on solvation free energy, dipole moment, polarizability, hyperpolarizability and different molecular properties like chemical hardness & softness, chemical potential, electronegativity and electrophilicity index of metronidazole have been reported in this paper. Becke, 3-parameter, Lee-Yang-Parr (B3LYP) level of theory with 6-31G (d,p) basis set was applied for gas phase and solution. The effect of solvent polarity on solvation free energy, dipole moment, polarizability, hyperpolarizability and molecular properties were calculated by employing Solvation Model on Density (SMD). The solvation free energies and dipole moment of metronidazole were found to be increased in nonpolar to polar solvents. The dipole moment of metronidazole was higher in different solvent than that of the gas phase. Moreover, from non-polar to polar solvents the chemical potential, electronegativity and electrophilicity index were increased. On the other hand, opposite relation was found in the case of chemical hardness and softness. The results obtained in this study may lead to understand the stability and reactivity of metronidazole and the results will be of assistance to use the title molecule as reaction intermediates and pharmaceuticals. Bangladesh Pharmaceutical Journal 19(1): 9-14, 2016